Traditional Tanning Craft in Buraidah City during (1322-1402AH/1904-1982AD) - Alseadoon, Abdulkarim Mohammad; Al-Atni, Soliman Mohammed (Journal of Humanities & Social Sciences, 2025)
This study explores the traditional craft of tanning in the city of Buraidah during the 14th century AH (20th century CE), as one of the most vital handicrafts that the local community relied upon for processing animal hides into usable daily products. The research highlights the stages of tanning, starting from collecting and cleaning the hides, through treatment with natural organic materials such as Artemisia, dates, and animal oils, and ending with the softening and preparation of the leather for various industries. It also presents the tools used in this craft, the types of leather, the division of labor, and the main locations where tanning was practiced in Buraidah. The study draws upon oral interviews with craftsmen and local historians, in addition to authentic heritage sources and field documentation. Through this data, the research reveals the position of tanning within Buraidah’s economic cycle and its impact on complementary industries such as leatherworking and the production of sandals and other leather goods. This study is also framed within a broader national vision that supports the documentation of traditional crafts and industries, particularly following the approval of His Royal Highness Prince Mohammed bin Salman bin Abdulaziz Al Saud — Crown Prince and Prime Minister — may God protect him — to designate 2025 as the “Year of Handicrafts.” This royal endorsement reinforces the cultural urgency and academic value of such studies in preserving national memory and safeguarding Saudi Arabia’s intangible cultural heritage.